PENGARUH CURRENT RATIO, DEBT EQUITY RATIO, NET PROFIT MARGIN DAN TURN ASSET TURNOVER TERHADAP HARGA SAHAM (Studi Empiris pada Sektor Properti yang Terdaftar di Bursa Efek Indonesia Periode 2019–2023)” - Ibrahim, Dafa Maulana; Syah, Muhammad Jusman (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The stock price is the value applied to a particular stock, which is generally set by the participants in the capital market or stock exchange at a specific time. The purpose of this study is to investigate how independent variables, Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Total Asset Turnover, affect the dependent variable, i.e. share price, in the property sector companies listed on the Indonesian Stock Exchange. Sampling used in this study using purposive sampling techniques, the population on this study represents the entire property sectore company listed at the Indonesian Stock Exchange in 92 companies and the sample used in this study amounts to 48 property companies, and the data used for this study are obtained from the financial reports published by Indonesian Stock Exchange in the period 2019-2023. Using Multiple Linear Regression Analysis The result of this study that the Current Ratio variable has no influence on the Stock Price, the Debt to Equity Ratio has an influence upon the Stock price, the Net Profit Margin has an impact on the Share Price, and the Total Asset Turnover has no effect on the stock price